2009
DOI: 10.1108/02686900910924563
|View full text |Cite
|
Sign up to set email alerts
|

The audit trinity: the key to securing corporate accountability

Abstract: PurposeThe purpose of this paper is to distinguish between corporate accountability and corporate governance, explore the development of corporate accountability and examine the role of the tripartite audit function in securing this accountability.Design/methodology/approachA normative approach has been adopted and the research is based, primarily, on an examination of relevant literature.FindingsSociety facilities the growth of economic entities by providing them with resources. As their command over resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 12 publications
2
37
0
1
Order By: Relevance
“…These developments resulted in calls by politicians, the media and society in general (in the UK and NZ, as elsewhere) for greater corporate accountability and responsible corporate governance – and for external auditors to play a more active role in combating corporate ills (Porter, 1997, 2009). Responding to these calls in the UK, in 1991 the Financial Reporting Council (FRC), the London Stock Exchange and the Institute of Chartered Accountants in England and Wales (ICAEW) established the Committee on the Financial Aspects of Corporate Governance (CFACG; Cadbury Committee).…”
Section: Changes In the Structure And Composition Of The Audit Expmentioning
confidence: 99%
See 1 more Smart Citation
“…These developments resulted in calls by politicians, the media and society in general (in the UK and NZ, as elsewhere) for greater corporate accountability and responsible corporate governance – and for external auditors to play a more active role in combating corporate ills (Porter, 1997, 2009). Responding to these calls in the UK, in 1991 the Financial Reporting Council (FRC), the London Stock Exchange and the Institute of Chartered Accountants in England and Wales (ICAEW) established the Committee on the Financial Aspects of Corporate Governance (CFACG; Cadbury Committee).…”
Section: Changes In the Structure And Composition Of The Audit Expmentioning
confidence: 99%
“…During the past 100 or so years, criticism of external auditors and loss of confidence in their work have been fuelled by the unexpected demise of major companies shortly after receiving an unqualified audit report and by well‐publicised cases of corporate fraud of which the auditors gave no warning (Carty, 1985; Russell, 1986; Chandler & Edwards, 1996; Porter, 2009). The criticism and loss of confidence in auditors results from their failure to fulfil the responsibilities expected of them by society 1 – that is, from the audit expectation‐performance gap 2…”
Section: Introductionmentioning
confidence: 99%
“…While some support a formal auditing protocol (Morimoto et al 2005), and accounting professionals have proposed incorporating social auditing within their functions (Porter 2009;Savitz and Weber 2006), others have suggested that public auditors are not the proper professionals for the job (Henriques 2001;O'Dwyer 2001) and that social scientists should have an important role (Boele and Kemp 2005). Regardless of who performs an audit, when a system for accountability is enforced there is a tendency to massage the information provided in order to fit the process (Neyland 2007).…”
Section: Transparency and Corporate Social Responsibilitymentioning
confidence: 96%
“…It is of importance to address this question, because competent and independent ACs can strengthen and maintain investor confidence in financial information and markets (Davidson, Xie & Weihong, 2004; DeFond, Hann & Hu, 2005; Porter, 2009). Since investor confidence in capital markets is a prerequisite for widely available sources of funding and the evolution of capitalism and prosperity (Bernstein, 2004), European policymakers and corporations should have a keen interest in specifying AC design standards that contribute to AC effectiveness and legitimacy.…”
Section: Introductionmentioning
confidence: 99%